Phytoremediation of Microplastics: A Perspective on Its Practicality - Tang, Kuok Ho Daniel (Industrial and Domestic Waste Management, 2023)
Microplastics have permeated all parts of the environment, rendering their removal essential. Numerous strategies ranging from the physical removal of mismanaged plastic items to the biodegradation of microplastics with microorganisms and biocatalysts have been proposed to alleviate microplastic pollution. Phytoremediation is one of the plastic-removing strategies, but it has not received much attention. This perspective paper aims to review the phytoremediation of microplastics and discuss its practicality. The paper shows that plants could act as interceptors and a temporary sink of microplastics by facilitating their deposition, adsorbing them, trapping them in the root zone, enabling them to cluster on the roots, taking them up, translocating them, and accumulating them in various plant parts. However, there was a lack of evidence pointing to the degradation of microplastics after they were adsorbed, taken up, and stored. Weak adsorption and environmental factors may cause the trapped microplastics to desorb, resuspend, or evade, thus also making plants a source of microplastics. The microplastics trapped and accumulated in plants may be transferred to the higher trophic levels of the food chain through ingestion and raise concerns over their ecotoxicities. Unlike localized pollution, microplastic pollution is widespread, which limits the applicability of phytoremediation. Besides, microplastics could adversely impact plant health and the ability of plants to remove other environmental pollutants. These drawbacks may reduce the attractiveness of phytoremediation unless it can be effectively combined with bioremediation to degrade microplastics.